Does migration stimulate human capital investment Theory and evidence - Herbert Brücker; Cécily Defoort; Carola Gruen (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
This paper investigates whether international migration stimulates additional investment in human capital in host countries. First, a simple theoretical model is developed, showing that if migration were allowed, additional human capital investment is possible. Whether human capital endowment in host countries will rise or fall, is an open problem. This result differs from traditional theories of brain drain which typically assume an exogenous level of human capital investment. The empirical part of the paper employs a newly collated data set. First results show that the share of the population investing in education increases with the share of highly qualified emigrants.
Keywords: F22; 330; International migration; Human capital; Labour market; Panel data econometrics